Antimicrobial resistance and biological properties of Staphylococci isolated from pigs - Yuriy VISHOVAN (Asociatia de Biosiguranta si Biosecuritate, 2020)
Introduction. Representatives of the genus Staphylococcus spp. cause a significant proportion of diseases in animals and humans. Nowadays the problem of their acquired antibiotic resistance is an urgent concern. Material and methods. Isolation and identification of Staphylococcus spp. carried out in accordance with DSTU EN 6888:2003 standard. The susceptibility of the strains to antibiotics was determined by the disk diffusion method. Interpretation of the results was carried out in accordance with the recommendations of the 8th version of EUCAST. Results. 77 strains of Staphylococcus spp. Collected from sows at farm No. 2, were isolated: hemolytic properties were detected in 90.6% (39 coagulases positive and 19 coagulase-negative); 22 (56.4%) strains of coagulase-negative Staphylococcus spp.; 13.6% of isolates had hemolytic properties. The results of antibiograms of crops from farm No.1: 51.8% of strains were susceptible to penicillin, 47.6% – resistant; 13.62 – susceptible to fluoroquinolones, 80.9% – resistant; 96.7% – susceptible to chloramphenicol, no resistant strains were detected. Conclusions. Acquired resistance of Staphylococcus spp. to certain groups of antibiotics isolated from pigs, indicated the irrational use of antimicrobial therapy. Differences were found in the susceptibility of coagulase-positive and coagulase-negative Staphylococcus spp. to all groups of antibiotics.